Capability and Potentials of Responsibility Centres Under the Implementation of Decentralisation Policy - Mohd Nor, Zanariah (2001)
The introduction of a decentralised system In a public university In 1995 was geared for capacity· building of Responsibility Centres (RCs) In overcoming some limitations of the centralised administrative system The decentralised system did not seem to achieve Its objectives when several problems emerged. The study was an attempt to examine the capability and potentials of RCs In administering and managing academic and support functions under the decentralised system In a public university The model of public policy, administration and finance by Rondinelli et al (1989, 1984) was used to guide the study process The study adopted a quantitative and a modified qualitative approach The study population comprised administrators at the academic RCs A total of 99 respondents and 16 Informants were Involved the quantitative and qualitative approaches respectively A self-administered questionnaire was used for the quantitative approach while the semi-structured Interview was used for the qualitative approach The quantitative data were analysed using the Statistical Package for Social Sciencever 75 while the qualitative data were analysed using the Ethnograph ver 5 Under the decentralised system, the study found that the RCs encountered several constraints related to bureaucratic,